Development of intelligent system for eye-tracking application - Lin, Zichun (2017)
This project was to build up an eye-tracking device for disabled people to surf the internet or do some writing work using word software by controlling their eyes, Epson Moverio BT-200 Smart Glasses was selected to use as basic hardware with one personal computer. This report explains how to set up hardware and software, smart glasses is main viewing device for users, computer is main processing device, there will be an extra USB camera aiming at user eye to track pupil motion, different actions will be done automatically according to the direction that pupil move, so there will be a lot of image processing in software part, Camshift is the main algorithm that used to track pupil. Now user can surf the internet with it by controlling eyes.